A comprehensive review on recent preparation techniques of liposomes. (1st October 2020) - Has, C.; Sunthar, P.
Abstract: Liposomes (or lipid vesicles) are a versatile platform as carriers for the delivery of the drugs and other macromolecules into human and animal bodies. Though the method of using liposomes has been known since 1960s, and major developments and commercialization of liposomal formulations took place in the late nineties (or early part of this century), newer methods of liposome synthesis and drug encapsulation continue to be an active area of research. With the developments in related fields, such as electrohydrodynamics and microfluidics, and a growing understanding of the mechanisms of lipid assembly from colloidal and intermolecular forces, liposome preparation techniques have been enriched and more predictable than before. This has led to better methods that can also scale at an industrial production level. In this review, we present several novel methods that were introduced over the last decade and compare their advantages over conventional methods. Researchers beginning to explore liposomal formulations will find this resource useful to give an overall direction for an appropriate choice of method. Where possible, we have also provided the known mechanisms behind the preparation methods.